2020
DOI: 10.1177/1129729820943076
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of routine ultrasound-guided percutaneous transluminal angioplasty in the treatment of native arteriovenous fistula dysfunction

Abstract: Background: Stenosis is the main cause of arteriovenous fistula failure and is due to neointimal hyperplasia. Percutaneous transluminal angioplasty is the gold standard for patients with vascular access stenosis. The aim of the study was to evaluate the efficacy and safety of ultrasound-guided percutaneous transluminal angioplasty in the treatment of native arteriovenous fistula venous stenosis. Methods: The need for intervention was determined by physical examination and duplex ultrasound in 162 patients. All… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…Primary patency rates at 6, 12, and 24 months were 87.7%, 75.8%, and 60.0%, respectively. These results are comparable to those reported in other literature [ 15 , 16 ], and also demonstrate the safety and effectiveness of UG-PTA.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Primary patency rates at 6, 12, and 24 months were 87.7%, 75.8%, and 60.0%, respectively. These results are comparable to those reported in other literature [ 15 , 16 ], and also demonstrate the safety and effectiveness of UG-PTA.…”
Section: Discussionsupporting
confidence: 91%
“…A previous study demonstrated that only reliable predictor of postintervention secondary patency loss was previously unsuccessful and abandoned AVF [ 12 ]. No similar finding was seen in any of the other studies that evaluated the predictors of postintervention primary patency [ 14 , 16 , 43 ]. It is probable that several factors relating to patient selection and standard surgical procedures played a part in the current study.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Currently, percutaneous transluminal angioplasty (PTA) is the primary management of malfunctional AVF, such as immature fistula [ 5 ], stenosis of fistula caused by neointimal hyperplasia [ 6 , 7 ], stenosis or occlusion of juxta-anastomosis [ 8 ], and AVF thrombosis [ 9 ].…”
Section: Introductionmentioning
confidence: 99%